Preparation, spectroscopic characterization of a new Cd(II) complex containing tridentate NNO Schiff base derived and X-ray crystallographic structural study of 3,4,5-trihydroxybenzoic acid[1-(pyridyl)-ethylidene] hydrazone - Alhadi A.A.; Shaker S.A.; Suleiman N.G.; Yehye W.A.; Ali H.M. (Sociedad Chilena de Quimica, 2023)
A new Cd(II) complex with a tridentate Schiff base derivative which was obtained from condensation of gallic hydrazid with 2-acetylpyridine has been prepared. The structure of the ligand 3,4,5-Trihydroxybenzoic acid[1-(pyridyl)-ethylidene]hydrazone (GAPy) was confirmed using the X-ray structure analysis. The elemental analysis, FTIR, UV-Vis, 1H NMR spectral and Thermal analysis indicates that the Schiff base ligand GAPy is a tridentate ligand which is coordinated with the Cd(II) complex through N,N and O atoms. Thus, the acetate ion is a bidentate ligand that is coordinated with the metal ion through two O atoms.